Understanding youths' needs for digital societal participation: towards an inclusive Virtual Council. Issue 5 (4th April 2021) - Pietilä, Iikka; Meriläinen, Niina; Varsaluoma, Jari; Väänänen, Kaisa
ABSTRACT: It is important for the sustainability of society that everyone can participate in societal discussions. Although a plethora of services exists for digital participation, they have not proven to entice a broad range of youths to contribute. The aim of this research is to investigate how digital tools can offer inclusive ways for youth to take part in societal processes. We present a study of young people's needs for a digital service enabling societal participation. Altogether 74 young people aged 16–27 with varying backgrounds participated in six workshops. Scenarios were used as stimulus materials for eliciting participants' feedback on digital participation. The findings bring up youth's needs for such service. Needs such as having a safe environment for discussions and making the effect of participation visible were found. Finally, the findings and resulting Virtual Council prototype are presented and discussed, and their significance in advancing inclusive digital societal participation are elaborated.